Upaya Peningkatan Pelafadzan Mahrojul Huruf Dengan Metode Talaqqi Pada ABK di SMPIT Logaritma Karanganyar - Ahmad Wakhid Hasyim; Apihun Apihun; Syahid Husam Rahmat Tulloh; Siti Fatimah (IAINU Kebumen, 2023)
This study aims to determine the increase in the pronunciation of makhorijul letters especially hijaiyyah letters in children with special needs through the Talaqqi method at SMPIT Logaritma Karanganyar. This type of research is Classroom Action Research (CAR), which will be conducted from May 2023 to June 2023. This research consists of two cycles with four main activities in each cycle, namely planning, action, observation, reflection. Data were analyzed using quantitative data. The subjects in this study were children with special needs at SMPIT Logaritma Karanganyar. Totaling 3 children. The data collection technique used is the observation technique. Observations were made directly at SMPIT Logaritma Karanganyar. The results of the analysis showed an increase, namely in the first cycle there were 35% of students getting an increased pass score, in the second cycle there were 90% of students getting a complete score. So it can be concluded that the talaqqi method can improve the pronunciation of makhorijul letters of interest in children with special needs at SMPIT Logaritma Karangayar